أثر استخدام استراتيجية التعلم المستقل في تنمية مهارة التعبير الكتابي لدى طالبات قسم الإعداد اللغوي بجامعة الراية - Syafrina Bakti; Rizal Firdaus (Rayah Al-Islam, 2019)
The purpose of this study to know the independent learning strategy used improve the writing skill of students at the preparatory department of STIBA Ar Raayah 2018/2019. To achieve this objective, the writer used observational method to measure the influence of using the individual study strategy in improving the writing skill by conducting a test to a sample of 30 students who were chosen randomly at the preparatory department Ar Raayah. This study prove many results, the firsth: that strategic independent learning gave an effective influence developing Arabic writing skill of students at the preparatory department Ar Raayah. The second, improving the study of ten writing skills for the preparatory students. The third, analysis result of experimental group higher than the control group in four points; using the punctuation is 6,7%, using the conjuction sign is 20%, choosing the main of idea in a paragraph is 26,66%, and describing the picture is 20%.